2014
DOI: 10.1186/1471-2164-15-117
|View full text |Cite
|
Sign up to set email alerts
|

Systematic characterization of small RNAome during zebrafish early developmental stages

Abstract: BackgroundDuring early vertebrate development, various small non-coding RNAs (sRNAs) such as MicroRNAs (miRNAs) and Piwi-interacting RNAs (piRNAs) are dynamically expressed for orchestrating the maternal-to-zygotic transition (MZT). Systematic analysis of expression profiles of zebrafish small RNAome will be greatly helpful for understanding the sRNA regulation during embryonic development.ResultsWe first determined the expression profiles of sRNAs during eight distinct stages of early zebrafish development by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 48 publications
3
28
0
Order By: Relevance
“…For example, a previous study showed that dre-let-7a and dre-miR-22a were among the top five most abundant miRNA families expressed in early zebrafish development. 36 Similarly, with a previous study, dre-let-7 and dre-miR-22a were highly expressed in zebrafish spermatozoa in our results. Also, dre-miR-430b, which facilitates the MZT by the clearance of maternal mRNAs, was identified in this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For example, a previous study showed that dre-let-7a and dre-miR-22a were among the top five most abundant miRNA families expressed in early zebrafish development. 36 Similarly, with a previous study, dre-let-7 and dre-miR-22a were highly expressed in zebrafish spermatozoa in our results. Also, dre-miR-430b, which facilitates the MZT by the clearance of maternal mRNAs, was identified in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Previous analysis of miRNAs showed that 218 known miRNAs and 25 novel miRNAs were detected during eight distinct stages of early zebrafish development by sRNA-seq technology. 36 Wei et al reported that 198 known miRNAs and 8 novel were identified during zebrafish early development. 37 In this study, we identified 400 novel and 204 known miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…The unexpected differences in the RNAi repertoire of bilaterians, cnidarians, ctenophores and sponges uncovered here, suggests that while the last common ancestor of extant animals employed miRNA, piRNA and endo-siRNA systems, these were not integrated into the shared ancestral gene regulatory system. This is in contrast to bilaterians, which in general appear to use a common RNAi system [10][11][12][13][14][15][16]. Following the emergence of these major metazoan RNAi pathways, lineage-specific evolutionary trajectories appear to have resulted in divergent RNAi strategies evolving in each basal metazoan lineage.…”
Section: Discussionmentioning
confidence: 95%
“…There are some marked differences in the miRNA systems of sponges, cnidarians and bilaterians. In contrast to bilaterians, which express a complex repertoire of miRNAs in somatic tissues [10][11][12][13][14][15][16], miRNA expression in cnidarians is consistently dwarfed by piRNAs [2,[17][18][19]. The miRNAs of the cnidarian Nematostella vectensis, while capable of bilaterian-like silencing [20], also regularly silence their targets through extensive base pairing followed by cleavage, as observed in plants, rather than by transcript destabilisation or translational inhibition [19].…”
mentioning
confidence: 99%
“…However, a good approximation can be obtained by examining miRNA sequencing data from whole animals at different developmental stages and complementing this with expression data of individual miRNAs. For example, sequencing data from whole embryos or larvae of C. elegans and zebrafish (Kato et al, 2009;Yao et al, 2014) show that a small fraction of miRNAs is highly abundant during at least one developmental stage, whereas the majority seems to be expressed at low levels (Fig. 3).…”
Section: Many Mirnas May Act At the Periphery Of Developmentmentioning
confidence: 99%